2021
DOI: 10.14710/jitaa.47.1.17-28
|View full text |Cite
|
Sign up to set email alerts
|

A New SNPs at 3’UTR Region of calpain 1 gene and its association with growth and meat quality traits in beef cattle

Abstract: The objective of this study was to evaluate single nucleotide polymorphisms (SNP) in the 3'UTR region of CAPN1 gene by direct sequencing technique in beef cattle and its influence on growth and meat quality of the contrast mode ultrasound image in Bali cattle. The numbers of beef cattle used were Bali cattle (n=52 heads) which compared to purebred Belgian Blue (n=30 heads), Limousine (n=14 heads), Wagyu (n=7 heads), and PO (n=10 heads). Genetic diversity data were obtained from calculations by PopGen 1.32 soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In addition, SNP g.3549G/A located in 3' untranslated regions (3'UTR) was not associated with WW, WSH, WBL, WCC, YW, YSH, YBL and YCC in Bali cattle. However, SNP g.15525 G>A in 3'UTR region of CAPN1 gene was associated with a backfat thickness in Bali cattle (Dairoh et al, 2022), this proves that 3'UTR region also affects economic traits in cattle but does not occur in SNP g.3549G/A of the leptin gene in Bali cattle. 3' untranslated region plays an important role in regulate mRNA-based processes such as influencing mRNA localization, mRNA stability, and efficiency of mRNA translation (Mayr, 2019).…”
Section: Association Of Leptin Gene With Growth Traits In Bali Cattlementioning
confidence: 79%
“…In addition, SNP g.3549G/A located in 3' untranslated regions (3'UTR) was not associated with WW, WSH, WBL, WCC, YW, YSH, YBL and YCC in Bali cattle. However, SNP g.15525 G>A in 3'UTR region of CAPN1 gene was associated with a backfat thickness in Bali cattle (Dairoh et al, 2022), this proves that 3'UTR region also affects economic traits in cattle but does not occur in SNP g.3549G/A of the leptin gene in Bali cattle. 3' untranslated region plays an important role in regulate mRNA-based processes such as influencing mRNA localization, mRNA stability, and efficiency of mRNA translation (Mayr, 2019).…”
Section: Association Of Leptin Gene With Growth Traits In Bali Cattlementioning
confidence: 79%
“…Dairoh et al (2021) stated that SNPs in the CAPN1 gene were associated with a marbling score in Bali cattle. Dairoh et al (2022) also stated that the 3'UTR region of the CAPN1 gene was found in 8 base deletions in Bali cattle. Furthermore, two specific SNPs in the ADIPOQ genes (c.-399C>T and c.-273C>G) showed potential as genetic markers of marbling score for Bali cattle (Sutikno et al, 2018).…”
Section: Introductionmentioning
confidence: 99%